"New media serving the teaching and learning process in the sport-scientific education" - An empirical study about the internet utilisation for the university sports scientific education - Knoch, R. (International Journal of Computer Science in Sport, 2003)
An `optimal' preparation of the students for the teaching practice with the new media necessarily demands corresponding `self-awareness ' in the own university education. The present empirical study tried to receive a present picture of the actual offers of Internet based lectures as well as of the personal suppositions and attitudes of the students (and teachers) concerning the Internet and computer utilisation for the university sports scientific education. Under this point of view at the winter term 2001/02 an analysis of the present Internet based teaching offers of the German institutes of sports science took place. The existing information concerning the sports scientific education had been classified in the following way: 1. The kind of implementation into the learning and teaching process, especially regarding the coupling degree of the Internet based information to the real lectures. 2. The ascription of the internet based lectures to the different sports scientific fields. 3. The localisation of the Internet based lectures in the structure of the websites.